Learning from our older people: Pilot study findings on responding to heat. (6th August 2013) - Loughnan, Margaret E.; Carroll, Matthew; Tapper, Nigel
<x xml:space="preserve">Abstract</x> Aims With the advent of climate change, it is important that strategies be put in place to minimise the effects of heat. These impacts can be compounded by other factors such as location and age. This exploratory pilot study focuses on older people in a rural Victorian community that regularly experiences hot weather. Method Mixed methods – including a focus group, household interviews, daily diaries and collection of meteorological data. Results The community is generally well adapted to heat with all having modified their homes and behaviours to cope with extreme heat. There was, however, little understanding or planning regarding the potential health impacts of heat. Conclusions There is a clear need for community‐directed adaptation to best meet the needs of older people, particularly those living in urban areas, and for targeted public health campaigns to increase awareness of heat‐health risks and disseminate the strategies identified in this community.